Evaluation of the Effectiveness of Sexuality Volunteer Cadre Training in Junior High School in Tombolo Pao, Gowa - Berlian, Berlian; Paramita, Irma Susan; Syahrir, Sukfitrianty; Karini, Tri Addya (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Indonesia is still a country with a large number of early marriage cases. The high number of cases shows that sexual education in preventing early marriage and improving adolescent reproductive health needs to be implemented. The training of volunteer sexuality cadres at SMPN 2 Tombolo Pao aims to increase students' knowledge and awareness of reproductive health and the dangers of early marriage. This program evaluation uses quantitative evaluation methods through pre and post-tests, observations, and interviews. The results of the analysis showed a significant increase in the knowledge of the cadres after the training. Interviews with the cadres indicated that this activity went well and that the cadres were able to educate their peers about the dangers of early marriage. However, the formation of an official cadre structure did not take place due to the constraints of preparing for exams and scout competitions. Observations showed that the physical intervention of installing posters at two strategic points was hampered by school renovations, so the posters were temporarily removed and will be reinstalled after the renovations are completed. The findings suggest that the sexuality volunteer cadre training is effective in increasing knowledge and information dissemination among students, although improvements are needed in the structural implementation and placement of educational materials in the school environment.